PENGARUH BRAND AMBASSADOR, BRAND PERSONALITY, DAN KOREAN WAVE TERHADAP KEPUTUSAN PEMBELIAN: (Studi pada Konsumen Produk Scarlett Whitening di Universitas Budi Luhur Jakarta) - Atik Nurfiana; Ravindra Safitra Hidayat (CV. Denasya Smart Publisher, 2024)
The purpose of this study is to ascertain how purchasing decisions are impacted by brand ambassadors, brand personalities, and the Korean wave. Utilizing quantitative methodology, data sources were gathered by means of questionnaire distribution. Students from the 2020 class at Budi Luhur University made up the study's population. Purposive sampling, a non-probability sampling approach, was used in the sampling process to gather 100 respondents using the Slovin formula. The findings indicated that purchasing decisions are significantly influenced by brand ambassadors, by brand personalities, and by the Korean Wave phenomena